A Safety Monitoring And Control System For Process Plant Using Programmable Logic Controller Via Function Block Diagram Programming - Abd. Rahaman, Siti Aisyah (IRC, 2015)
This project is about a safety monitoring and control system of process plant to provide better automated supervision for a plant with minimum human intervention in making decision depends on the plant’s status. The system is programmed by using functional block diagram (FBD) which is one of graphical language standardize by IEC 6133-3. The robustness of FBD makes it compatible to be use for system which required complex and critical decision making.